The Role of Woman in Black Beauty by Anna Sewell through Representation - Pariama, Stevane Delsancy; Sriastuti, Anna (Universitas Negeri Semarang, 2024)
Women often face stereotypes of being nurturing or empathetic due to their historical roles as caregivers, leading to unfair judgments based on emotions compared to men's rationality. Because of this situation Simone de Beauvoir, a French philosopher, later criticized gender inequality in her writing